PENGARUH KESADARAN PAJAK, TINGKAT PENDIDIKAN, DAN PERSEPSI TENTANG SANKSI PAJAK PENGUSAHA PENYEDIA JASA INTERNET TERHADAP KEPATUHAN FORMAL - Musrifah Novianti; Mienati Somya Lasmana (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2016)
This study aimed to determine the effect of tax awareness, education level, and the perception about tax penalties of entrepreneurs of internet service providers against formal compliance. The approach used is quantitative explanatory that focuses on hypothesis testing through multiple linear regression analysis. This study uses primary data in the form of questionnaires. The sample used in this study were 31 companies from the member Asosiasi Penyedia Jasa Internet Indonesia (APJII) East Java. The partial t test indicate that tax awareness and education level of entrepreneurs of internet service providers do not significantly influence formal compliance, while the perception about tax penalties of entrepreneurs of internet service providers significantly influence formal compliance.